Exploring Epigenetic Landscapes in COPD: Therapeutic Implications and Recent Insights - Wirawan, Aditya; Kinasih, Tutug; Imaniar, Rania; Baskoro, Hario; Antariksa, Budhi; Matsumoto, Naohisa (Respiratory Science, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a leading cause of global mortality, primarily driven by an abnormal inflammatory response to harmful particles and gases. This review explores the epigenetic mechanisms underlying COPD pathogenesis and their therapeutic implications. A comprehensive literature review was conducted, analyzing recent findings on DNA methylation, histone modifications, and noncoding RNAs (ncRNAs) in COPD. Key studies highlighting the impact of these epigenetic changes on inflammation, cellular responses, and disease progression were evaluated. Our review highlights that epigenetic modifications, such as DNA methylation and histone modifications, significantly impact gene expression without altering the DNA sequence. Cigarette smoking has been shown to influence both DNA methylation and histone acetylation, leading to inflammatory responses and the the exacerbation of COPD. These modifications contribute to chronic inflammation and disease progression, with alterations in histone acetylation, methylation, and phosphorylation playing critical roles in COPD pathogenesis. The interplay between epigenetic changes and environmental factors, particularly tobacco smoke, reveals a complex mechanism driving COPD progression. Aberrant gene expression linked to these epigenetic modifications suggests potential disease severity and progression biomarkers. Targeting these alterations offers novel therapeutic strategies. Emerging treatments, such as quercetin and theophylline, promise to restore normal cellular functions and effectively manage COPD. Future research should focus on elucidating these mechanisms further and developing targeted therapies to mitigate the impact of epigenetic modifications on COPD.